Impact of Irrigation Dams on Fish Diversity of Budhikhola in Bardiya, Lumbini Province of Nepal - Chaudhari, Bhesh Raj (Academia Research Journal, 2024)
This extensive study describes the current status of freshwater fish diversity in the Budhikhola which is an important branch of the Karnali River that runs through the western region of the Bardiya district covering about 30 km distance in the north-south direction. To examine the effects of irrigation dams on habitat modification and fish variety, fish were collected from the entire Budhikhola stretch, with four sampling stations established depending on habitat structure. The freshwater system of the Budhikhola harbors a diverse and ecologically complex fish community comprising 41 species from 6 orders and 13 families. The dominance of the Cyprinidae family, represented by Barilius barna, Chanda nama, Chagunius chagunio, etc., highlights its ecological significance. On the other hand, the loss of important fish species is proof that the building of irrigation dams has had significant ecological effects. Human-induced hazards such as damming and overexploitation, have adversely impacted the river environment, resulting in reduced water depth, habitat structure changes, and restricted nutrient flow. The majority of the riverbed had been observed to be silt-covered. Significant fish species loss indicates ecological instability brought on by human activity. Changes in the distribution of fish sizes and spatial differences between upstream and downstream areas highlight the complex link between habitat modifications and community functioning. The catch-per-hour seasonal tendency, which peaks in September and falls in March, is correlated with fishing patterns, environmental factors, or breeding seasons. The evenness value (0.96) and high Shannon-Weiner Diversity Index (H’= 3.57) show a diverse and harmonious fish community. The relevance of family-level distinctions in implementing effective conservation and management measures is highlighted by major differences among family groups (p<0.001). As the findings make clear, the long-term survival of the diversified fish ecosystem of the Budhikhola depends on addressing and reducing anthropogenic stressors. This study provides valuable insights for informed conservation efforts in the aquatic ecosystems of Nepal.